Fulfilling the promises of South Asian integration: A gravity estimation - Mustafa Moinuddin (Asian Development Bank Institute (ADBI), 2013)
In all the regions of the contemporary world - including Asia - there is a growing trend in market consolidation through regional collaboration in the form of bilateral and regional trade agreements. Regional cooperation and integration can facilitate the way for expanding markets and creating trade opportunities. However, market-led integration in South Asia lags behind other regions, even though the region's geography and comparative advantages offer the potential for a highly integrated trade, investment, and production space. The South Asian Association for Regional Cooperation (SAARC), which is the most important umbrella organization in the region, has taken several initiatives for enhancing integration - the South Asian Preferential Trading Arrangement (SAPTA), and the South Asian Free Trade Area (SAFTA), and more recently the SAARC Agreement on Trade in Services (SATIS), which was signed in 2010 (SAARC Secretariat 2004, 2010). It is early days, but there is statistical evidence suggesting that intra-regional trade among the SAFTA members is rising slowly but surely. Policymakers as well as business communities across the South Asian region have become increasingly interested in SAFTA and its potential benefits. The purpose of this paper is to examine the determinants and trade effects of SAFTA using empirical methods. It begins with an overview of South Asia for a general understanding of the state of the region's economy and trade as well as the recent progress in global and regional integration of the South Asian economies. The paper then proceeds to review some of the relevant studies on South Asia's trade integration within the context of the empirical methods used in analyzing trade effects of regional instruments. An empirical specification of the gravity model is developed in the next section to analyze the determinants of trade flows for the SAFTA countries. Based on the results of the modeling exercise, the concluding section of the paper discusses the policy implications of SAFTA, highlighting the need for maintaining the primacy of economic integration in the region's growth and development processes. The paper argues that the recent success in the growth performance of the South Asian countries offers prospects as well as challenges for deeper integration with the global economy. Integration under the SAFTA is, South Asia must understand, the first step in that direction.
Keywords: F13; F14; F15; 330; south asia; trade; free trade agreement; fta; regional integration; Handelsabkommen; Regionale Wirtschaftsintegration; Makroökonomischer Einfluss; Gravitationsmodell; Südasien